2021
DOI: 10.1073/pnas.2015786118
|View full text |Cite
|
Sign up to set email alerts
|

Zn 2+ influx activates ERK and Akt signaling pathways

Abstract: Zinc (Zn2+) is an essential metal in biology, and its bioavailability is highly regulated. Many cell types exhibit fluctuations in Zn2+ that appear to play an important role in cellular function. However, the detailed molecular mechanisms by which Zn2+ dynamics influence cell physiology remain enigmatic. Here, we use a combination of fluorescent biosensors and cell perturbations to define how changes in intracellular Zn2+ impact kinase signaling pathways. By simultaneously monitoring Zn2+ dynamics and kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 74 publications
0
40
0
1
Order By: Relevance
“…Its elevated expression leads to an increase in intracellular zinc concentration, promoting MAPK phosphorylation in immune cells. 28 Increased intracellular zinc concentration also promoted ERK phosphorylation by Zn 2+ -mediated inhibition of phosphatases 29–31 ; ERK upstream kinases (eg, MEK) and Akt were robustly activated by cytosolic zinc as well. 29 MAPK, such as ERK1/2, responds to external stimuli and is intimately associated with numerous cell functions.…”
Section: Discussionmentioning
confidence: 98%
“…Its elevated expression leads to an increase in intracellular zinc concentration, promoting MAPK phosphorylation in immune cells. 28 Increased intracellular zinc concentration also promoted ERK phosphorylation by Zn 2+ -mediated inhibition of phosphatases 29–31 ; ERK upstream kinases (eg, MEK) and Akt were robustly activated by cytosolic zinc as well. 29 MAPK, such as ERK1/2, responds to external stimuli and is intimately associated with numerous cell functions.…”
Section: Discussionmentioning
confidence: 98%
“…U2OS cells expressing HaloTag-GR (stable overexpression) or HaloTag-CTCF (CRISPR-edited endogenous expression) were treated with either 50 µM of the Zn 2+ chelator TPA to deplete free Zn 2+ , 30 µM ZnCl2 to increase free Zn 2+ , or a media-only control for 30 mins. Previously, we have shown that these perturbations decrease labile Zn 2+ to <1 pM or increase labile Zn 2+ to 30 nM, respectively 22,23,37 . Under our imaging conditions, we were able to acquire between 493-1080 total tracks for HaloTag-GR and between 5065-12770 tracks for HaloTag-CTCF (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…For example, it's been shown that the nuclear hormone receptors glucocorticoid receptor (GR) and estrogen receptor (ER) contain two C4 Zn 2+ fingers bind Zn 2+ with KDs of 316 and 501 pM, respectively 21 . Given that it has been shown that cells experience changes in the labile Zn 2+ pool [22][23][24][25][26][27] , it is important to establish whether other Zn 2+ finger TFs are susceptible to changes in the Zn 2+ pool.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible scenario is that perturbation of intracellular zinc distribution induced by ZnT86D knockdown affects cellular signaling, and consequently, adversely affects neuronal survival. A recent study on the importance of zinc fluctuations in cellular signaling strongly supports this possibility [ 66 ]. This study shows that at the single cell level, changes in intracellular zinc levels occur in response to subtle extracellular perturbations, and these changes directly correlate with changes in ERK and Akt activity [ 66 ].…”
Section: Discussionmentioning
confidence: 88%
“…A recent study on the importance of zinc fluctuations in cellular signaling strongly supports this possibility [ 66 ]. This study shows that at the single cell level, changes in intracellular zinc levels occur in response to subtle extracellular perturbations, and these changes directly correlate with changes in ERK and Akt activity [ 66 ]. Since ZnT7 is important for the movement of zinc from the cytoplasm to the Golgi [ 23 , 24 ], the cellular distribution of zinc would be changed by ZnT86D knockdown, which may affect the activity of the ERK and Akt signaling pathways.…”
Section: Discussionmentioning
confidence: 88%